Penguatan Kemampuan Sosial-Emosional dan Kemandirian pada PPKS Disabilitas Melalui Pendekatan Psikoedukasi dan Kreatif di Sentra Budi Perkasa Palembang - Deany Afriany; Syakira Inayah Nayra; Zia Maharani; Nurul Faradyah; Nabila Khoirunisa; Putri Patma Sari (CV. Era Digital Nusantara, 2026)
This community service activity aimed to strengthen the social-emotional abilities and independence of Persons with Social Welfare Problems (PPKS) with disabilities through psychoeducational and creative approaches at Sentra Budi Perkasa Palembang. The program was designed to address the limited ability of participants in recognizing emotions, interacting socially, expressing feelings, and developing daily living independence. The methods used in this activity included participatory observation, psychoeducation, mentoring, creative activities, and social interaction exercises carried out through several programs such as emotional box, tree of hope, mini story theater, fun science day, happy journal, mental guidance sessions, and vocational skill activities. The implementation involved active collaboration between students, social workers, and beneficiaries in a supportive and inclusive environment. The results of the community service showed that the psychoeducational and creative approaches contributed positively to the improvement of participants’ social-emotional skills and self-confidence. Participants demonstrated better emotional expression, increased participation in group interactions, improved communication, and stronger motivation to engage in daily activities independently. Creative-based activities also encouraged participants to develop cooperation, self-expression, and adaptive behavior in a more enjoyable learning atmosphere. In addition, the program helped create a more supportive social environment within the rehabilitation center and enhanced students’ practical competencies in psychological assistance and social empowerment. Therefore, psychoeducational and creative interventions can become effective strategies for supporting the psychosocial development and independence of PPKS with disabilities in rehabilitation settings.